CORRELATION OF DRY EYES WITH ON-SCREEN TIME AMONG MEDICAL STUDENTS - NEHA SRIVASTAVA; LALIT SACHDEVA; SWATI AGARWAL; NEHA PEDNEKAR; SRIVASTAVA AK (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: An increased global dependence on digital screen use has resulted in a tremendous increase in screen-related ocular complaints such as dryness, ocular strain, burning sensation, grittiness, and transient blurring. This study aims to focus on the correlation between the duration of screen exposure and dry eyes among young medical students with the help of the combination of a questionnaire based on subjective symptoms of dry eyes and screen time and further tests to confirm dry eyes in those having symptoms. Numerous mechanisms have been mentioned in screen-associated evaporative dry eyes, including reduced blink rate, hazardous effects of blue light emitted from digital screens, and inflammatory changes. Methods: A cross-sectional study was conducted among 253 medical students at MIMS, Uttar Pradesh, from January 2021 to December 2022. Upon obtaining informed consent, all participants were given Schirmer 1 and tear film breakup time (TBUT) test. Patients with Schirmer 1 and TBUT reading <10 mm were identified as dry-eye patients. After that, a pre-designed questionnaire was applied to all dry-eye participants that asked about different symptoms of dry eyes and screen time and the correlation between subjective symptoms of dry eyes, dry-eye tests, and screen time was evaluated. Results: About 20.8% of medical students had dry eyes, and those who used their phones for 2–5 h had statistically higher rates of the condition. The length of breaks was also found to be strongly correlated with dry eye. Conclusion: Prolonged duration of digital screen exposure in any form (laptop and mobile phones, etc.) is directly related to the risk of dry-eye disease in the long term. Majority of the students (75%) were willing to reduce their screen time as a preventive measure toward dry eye.